Chemical alterations and regulations of biomolecules in lifestyle-related diseases. Issue 6 (2nd June 2016) - Miyoshi, Noriyuki
Abstract: We know experientially that not only nutrient factors but also non-nutritive functional food factors are playing important roles in maintenance of homeostasis, health promotion, and disease prevention. Although some of these effective behaviors are supported by accumulating scientific evidences, it is in general difficult to determine properly in human. Therefore, the discovering of novel biomarker and developments of the analytical method are one of the prudent strategies to understand disease etiology and evaluate efficacies of functional food factors via monitoring the pathophysiological alteration in live body, tissue, and cells. This review describes recent our findings on (1) formation mechanism, bioactivities, quantitative determination of cholesterol ozonolysis product, secosterol as possible biomarker for lifestyle-related disease, and (2) chemical biology approach for the investigating molecular mechanisms of most promising cancer chemopreventive food factors, isothiocyanate-inducing bioactivities. Graphic abstract: : Analytical scheme for the identification of ITC-binding molecules